The Role of Public Relations in the KRG Institutions Regarding the Political Conflict between Erbil & Baghdad - Karwan Mohammad Saber; Hoshyar Muzaffar Ali; Mohammad Khader Mouloud (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research is about the role of public relations in the institutions of the Kurdistan Regional Government, regarding the political conflict between Erbil and Baghdad. This research is descriptive research that is suitable with the research method, to achieve the objectives, the researcher used the survey method. The research group includes the public relations department of the ministries and agencies of the Kurdistan Regional Government. The sample of the study is (91) employees of the public relations department of both sexes, who were randomly selected. This study is a reason to focus on the role and responsibilities of the public relations department in the institutions of the Kurdistan Regional Government in the political conflict between Erbil and Baghdad. The aim of this study is to highlight the role of the Kurdistan Regional Government’ (KRG's) public relations in the conflict between Erbil and Baghdad. It also identifies the role of the KRG's public relations in managing the political conflicts between Erbil and Baghdad. The researcher concluded that the establishment of an institutional system is considered necessary, taking into account the current situation, public relations have an effective role in managing the conflict between Erbil and Baghdad. According to the research sample, public relations employees in the KRG have a role in explaining the facts, as well as in planning, communication, coordination and evaluation.